Founder mutation in myosin-binding protein C with an early onset and a high penetrance in males - Raquel Yotti; Francisco Fernández-Avilés; Javier Bermejo; Ana Isabel Fernandez; Cristina Gómez; Constancio Medrano; Irene Méndez; Maria Ángeles Espinosa; Sofía Cuenca; Rebeca Lorca; José Fernando Rodríguez; Maria Tamargo; et al. (Open Heart)
Objective One of the challenges in hypertrophic cardiomyopathy (HCM) is to determine the pathogenicity of genetic variants and to establish genotype/phenotype correlations. This study aimed to: (1) demonstrate that MYBPC3 c.2149–1G>A is a founder pathogenic variant, (2) describe the phenotype and clinical characteristics of mutation carriers and (3) compare these patients with those with the most frequent pathogenic HCM variants: MYBPC3 p.Arg502Trp/Gln.Methods We reviewed genetic tests performed in HCM probands at our institution. We carried out transcript analyses to demonstrate the splicing effect, and haplotype analyses to support the founder effect of MYBPC3 c.2149–1G>A. Carriers with this mutation were compared with those from MYBPC3 p.Arg502Trp/Gln in terms of presentation features, imaging and outcomes.Results MYBPC3 c.2149–1G>A was identified in 8 of 570 probands and 25 relatives. Penetrance was age and sex dependent, 50.0% of the carriers over age 36 years and 75.0% of the carriers over 40 years showing HCM. Penetrance was significantly higher in males: in carriers older than 30 years old, 100.0% of males vs 50.0% of females had a HCM phenotype (p=0.01). Males were also younger at diagnosis (32±13 vs 53±10 years old, p<0.001). MYBPC3 c.2149–1G>A resulted in an abnormal transcript that led to haploinsufficiency and was segregated in two haplotypes. However, both came from one founder haplotype. Affected carriers showed a better functional class and higher left ventricular ejection fraction (LVEF) than patients with MYBPC3 p.Arg502Trp/Gln (p<0.05 for both). Nevertheless, the rate of major adverse outcomes was similar between the two groups.Conclusions MYBPC3 c.2149–1G>A splicing variant is a founder mutation. Affected males show an early onset of HCM and with higher penetrance than women. Carriers show better functional class and higher LVEF than MYBPC3 p.Arg502Trp/Gln carriers, but a similar rate of major adverse outcomes.